2003
DOI: 10.1086/374841
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Hepatitis C Virus Coinfection in a Human Immunodeficiency Virus Clinical Trials Group: The Terry Beirn Community Programs for Clinical Research on AIDS

Abstract: The baseline prevalence of hepatitis C virus (HCV) and human immunodeficiency virus (HIV) coinfection among 2705 patients enrolled in HIV clinical trials in the Community Programs for Clinical Research on AIDS (CPCRA) was 16.6%. For men, multivariate logistic regression showed that the baseline prevalence of HIV-HCV coinfection was positively associated with history of injection drug use, older age, antiretroviral therapy naive status, African American or Latino ethnicity, and no history of having sex with men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 25 publications
4
29
1
2
Order By: Relevance
“…On the other hand, sexual transmission of HCV is relatively inefficient, and the rate of coinfection among HIV-infected patients with a sexual risk factor is less than 10% (61). Men who have sex with men do not seem to have an overall-increased risk for coinfection (21,61,121), although epidemics of acute HCV have been described for HIV-infected men who have sex with men with high-risk behaviors (33). The overall burden of coinfection is estimated at 4 to 5 million people worldwide (2).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, sexual transmission of HCV is relatively inefficient, and the rate of coinfection among HIV-infected patients with a sexual risk factor is less than 10% (61). Men who have sex with men do not seem to have an overall-increased risk for coinfection (21,61,121), although epidemics of acute HCV have been described for HIV-infected men who have sex with men with high-risk behaviors (33). The overall burden of coinfection is estimated at 4 to 5 million people worldwide (2).…”
Section: Epidemiologymentioning
confidence: 99%
“…Thus, the risk factors of the population under study directly influence the prevalence in that particular population. Parenteral exposure modes such as intravenous drug use (IVDU) or multiple transfusions have been consistently found to be the most important risk factors for coinfection (121). In HIV-positive patients with a history of IVDU, the rate of HCV infection is reported to be 82 to 93% (61,76,113).…”
Section: Epidemiologymentioning
confidence: 99%
“…5 Interestingly, this rate of coinfection has varied significantly worldwide depending on facilitating risk factors such as IDUs, geographic regions, risk groups, and exposure type, which may be different in each region of the same country.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the advent of HIV/AIDS in Nigeria, there was lack of enforcement of regulation guiding blood transmission in many localities; this enhances the indiscriminate blood transfusion practice and dominance of commercial donors among blood donor. Parenteral exposure modes such as intravenous drug use (IVDU) or multiple transfusions have been consistently found to be the most important risk factors for coinfection, (Tedaldi.,2003).Available data showed that the prevalence of hepatitis C virus among local commercial blood donor in Nigeria ranged from 12.3-14.0 % (Ajayi 1992).…”
Section: Introductionmentioning
confidence: 99%